Perceptions of accelerated Bachelor of Science in nursing program graduates regarding andragogical practices employed by faculty. - Hanson-Zalot, Mary E. (Perceptions of Accelerated Bachelor of Science in Nursing Program Graduates Regarding Andragogical Practices Employed By Faculty, 2016)
This research study was designed to examine accelerated, second-degree prelicensure baccalaureate graduates' perceptions of the andragogical practices employed by faculty that prepared students best to begin practice as entry level professional nurses. The study further sought to identify the ways in which andragogical practices used by faculty incorporated the students' prior learning and life experiences as they accrued knowledge of the art and science of nursing. It was anticipated that through the processes of interviewing and listening to the voices of graduates, that an emic perspective of the perceptions of the graduates would emerge. Analysis and interpretation of the results of this study demonstrated six key themes related to the educational experience. Perhaps most significantly, findings revealed that elements external to teaching strategy such as faculty attributes and program design influenced learning significantly for the study participants. This research adds to the existing body of literature related to the education of accelerated, second-degree prelicensure baccalaureate students. Findings of this study can be used to inform faculty about best practices for teaching this particular cohort of students who seek nursing as an alternate career and assist with innovative curricular designs to meet the needs of this unique group. Keywords: accelerated nursing programs, nursing education, second-degree students, teaching practices.